Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.24093/awej/call7.22
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Technology in Teaching of Writing Among Malaysian ESL Secondary School Teachers

Abstract: The application of technology in education has become a significant option for a more efficient and interactive approach, particularly in language teaching. However, few studies have investigated the use of technology in the teaching of writing in English language classrooms, especially in the Malaysian context. The present study investigates the teaching of writing practices and technology tools employed by English as a second language teachers when teaching writing skills. Using Technology Acceptance Model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…In light of the observations and the interview, the three instructors provided different ways of implementing technological tools in a writing classroom. Previous studies also reported similar findings (An & Williams, 2010;Riasati et al, 2012;Tze Pheng et al, 2021;Yunus et al, 2013). For instance, Ms. Carla employed Dropbox, Microsoft PowerPoint, Microsoft Word, emails, and the Internet in her classroom.…”
Section: Teaching Writing Strategiessupporting
confidence: 71%
See 2 more Smart Citations
“…In light of the observations and the interview, the three instructors provided different ways of implementing technological tools in a writing classroom. Previous studies also reported similar findings (An & Williams, 2010;Riasati et al, 2012;Tze Pheng et al, 2021;Yunus et al, 2013). For instance, Ms. Carla employed Dropbox, Microsoft PowerPoint, Microsoft Word, emails, and the Internet in her classroom.…”
Section: Teaching Writing Strategiessupporting
confidence: 71%
“…Some studies also focused only on providing benefits of implementing technology in the writing classroom in different disciplines (Kutlu, 2013). In an ESL context, most studies investigated the effect of technological tools on students' writing (Al-Wasy, 2020;Bikowski & Vithanage, 2016;Tze Pheng et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have examined the use of mobile learning in improving students' writing skills. Pheng, Hashim and Sulaiman (2021) clarified that online writing is a new approach that needs to be taught among Malaysian students to foster their writing abilities. Students are very technology savvy.…”
Section: Incorporation Of Mobile Learning Into English As a Second La...mentioning
confidence: 99%
“…The education system's goal in the present system is to provide complex learning environments for students by integrating authentic learning methods to develop their skills. Teachers need to emphasise using new approaches to deliver any subject content to their students in this new era, using technology applications to help students achieve excellence in education (Pheng et al,2021). Furthermore, the correct learning methods according to student's interests and abilities are tremendously important as they are helped to solve any complex problems they face in real life.…”
Section: Introductionmentioning
confidence: 99%